Eugenia uniflora L. seedling production by cutting: substrate, sazonality, auxine and rejuvenation methods - Cipriano, Roger; Tomazzoli , Maíra Maciel; Tofanelli, Mauro Brasil Dias; Santos, Bruno Francisco Sant’Anna; Ribas , Katia Christina Zuffellato; Deschamps, Cícero (Comunicata Scientiae, 2022)
Eugenia uniflora is a species that presents great phytochemical variability, due to its main form of propagation, the seminal, which makes the cultivation of this commercial crop unfeasible. Therefore, the objective of this work was to develop a protocol for vegetative propagation of Eugenia uniflora by stem cuttings. Substrates (Tropstrato®, vermiculite and sand), indolbutyric acid concentrations, rejuvenation methods (drastic pruning and minicutting) and harvesting times (winter, summer, autumn and winter) of the stems were compared. The highest rooting percentage and quality of the root system in cuttings were obtained when commercial substrate Tropstrato® and with some method of rejuvenation were used. The minicutting was more efficient, reaching almost 50% of rooting when collected in summer . Stem cuttings from plants that did not undergo any kind of rejuvenation, regardless of the time of collection, did not result in root formation. No anatomical changes were observed between cuttings from rejuvenated and non-rejuvenated plant material, indicating that the rhizogenic process did not occur in the cuttings originated from plants without rejuvenation because of biochemical and/or physiological reasons. The treatment of the stem cuttings with IBA did not result in increase of rooting, therefore the use of this plant regulator is not recommended.